Scale and ecosystem services: how do observation, management, and analysis shift with scale—lessons from Québec - Raudsepp-Hearne, Ciara; Peterson, Garry D. (Ecology and society, 2016)
Ecosystem service assessment and management are shaped by the scale at which they are conducted; however, there has been little systematic investigation of the scales associated with ecosystem service processes, such as production, benefit distribution, and management. We examined how social-ecological spatial scale impacts ecosystem service assessment by comparing how ecosystem service distribution, trade-offs, and bundles shift across spatial scales. We used a case study in Québec, Canada, to analyze the scales of production, consumption, and management of 12 ecosystem services and to analyze how interactions among 7 of these ecosystem services change across 3 scales of observation (1, 9, and 75 km²). We found that ecosystem service patterns and interactions were relatively robust across scales of observation; however, we identified 4 different types of scale mismatches among ecosystem service production, consumption, and management. Based on this analysis, we have proposed 4 aspects of scale that ecosystem service assessments should consider.